2016
DOI: 10.1039/c6sm00569a
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive properties of solvent molecules in the neighborhood of a polymer chain as seen by Monte-Carlo simulations

Abstract: The influence of both polymer chain length and concentration on the mobility of solvent molecules in polymer solutions was studied by Monte Carlo simulations with the use of the dynamic lattice liquid (DLL) model. The poly(vinylmethylether)-water system was used as a model. Two different solvent (water) states with differing mobilities were distinguished in polymer solutions. The first one with high molecular mobility independent of polymer concentration corresponds to bulk solvent in real systems. The second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 75 publications
1
24
0
Order By: Relevance
“…Diffusional exponents for the Power Law model (Equation 3) were estimated through plotting ln ( M t / M ∞ ) against ln ( t ) which are shown in Table . The diffusional exponent ( n ) and the diffusional constant ( k ) which characterizes the polymer network system (s −1 ) (Sangsuwan, Rattanapanone, Auras, Harte, & Rachtanapu, ) and depends on temperature as well as diffusant size (Kozanecki, Halagan, Saramak, & Matyjaszewski, ) were calculated from the slope of lines and the intercept, respectively. The determination coefficients ( R 2 ) indicating the deviation from the linearity plot of ln ( Mt / M ∞ ) versus ln ( t ) are also shown in Table .The diffusional exponents were between 0.5 and 1.0 for all types of active films representing anomalous or non‐Fickian transport, which is contribution of Fickian diffusion and controlled relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Diffusional exponents for the Power Law model (Equation 3) were estimated through plotting ln ( M t / M ∞ ) against ln ( t ) which are shown in Table . The diffusional exponent ( n ) and the diffusional constant ( k ) which characterizes the polymer network system (s −1 ) (Sangsuwan, Rattanapanone, Auras, Harte, & Rachtanapu, ) and depends on temperature as well as diffusant size (Kozanecki, Halagan, Saramak, & Matyjaszewski, ) were calculated from the slope of lines and the intercept, respectively. The determination coefficients ( R 2 ) indicating the deviation from the linearity plot of ln ( Mt / M ∞ ) versus ln ( t ) are also shown in Table .The diffusional exponents were between 0.5 and 1.0 for all types of active films representing anomalous or non‐Fickian transport, which is contribution of Fickian diffusion and controlled relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…This hopping mechanism has been indeed linked to the sub-diffusive behavior in various systems and has also been described in the context of diffusion in polymers. 27…”
Section: Diffusion In Molecular Models Of Hydrated Pvam Systemsmentioning
confidence: 99%
“…13 Sub-diffusive behavior of solvent in a system of charged polymer chains has been observed by Pandey et al, 25 Savage et al 26 described persistent sub-diffusive proton transport in hydrated perfluorosulfonic acid. Influence of chain length and polymer concentration on the extent of sub-diffusive behavior has been explored by Kozanecki et al 27 Sub-diffusion behavior of gas molecules in polymer matrices of different composition and morphology has been also observed and characterized by Anderson et al 28 More recently, Zhang et al 29 proposed a general model of transport in glassy polymers, carefully characterizing different regimes of diffusion and their relation to the behavior of polymer permeability and selectivity on the Robeson plot. 30 The objective of this study is to propose a plausible molecular model of an FTM, elucidate its structural organization on a molecular level, and explore properties of water confined in these structures as a function of the degree of hydration and the protonation state of the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown the reinforcement of nanocomposite materials with the aggregations of nanoparticles, the enhanced stiffening effect with increasing interfacial area between nanoparticles and polymer matrices, the change of polymer structures in the vicinity of nanoparticles, the decline in polymer motions, and the relation between the interactions and the fracture behavior . Polymer networks with attractive particles have been also studied by computer simulations in order to elucidate the characteristic properties of polymer gels such as the swelling behavior of polymer gels, cross‐linked structures, and diffusive properties . However, since there are a wide variety of polymer gels with sacrificial bonds of various mechanisms, we think that further studies concerned with sacrificial bonds are required.…”
Section: Introductionmentioning
confidence: 99%
“…[35,41] Polymer networks with attractive particles have been also studied by computer simulations in order to elucidate the characteristic properties of polymer gels such as the swelling behavior of polymer gels, [42][43][44][45] cross-linked structures, [46] and diffusive properties. [47] However, since there are a wide variety of polymer gels with sacrificial bonds of various mechanisms, we think that further studies concerned with sacrificial bonds are required.…”
Section: Introductionmentioning
confidence: 99%